Very early lineage-specific chimerism after reduced intensity stem cell transplantation is highly predictive of clinical outcome for patients with myeloid disease. (August 2019) - Kinsella, Francesca A.M.; Inman, Charlotte F.; Gudger, Amy; Chan, Yuen T.; Murray, Duncan J.; Zuo, Jianmin; McIlroy, Graham; Nagra, Sandeep; Nunnick, Jane; Holder, Kathy; Wall, Kerry; Griffiths, Mike; et al.
Graphical abstract: Highlights: Chimerism within PBMC and T cells at day 50 after allo-SCT defines three groups. Relapse risk for myeloid disease is high if mixed chimerism present in both subsets. This risk of relapse is 45% at 1 year with associated 5 year survival of only 40%. Abstract: Background: The importance of chimerism status in the very early period after hematopoietic stem cell transplantation is unclear. We determined PBMC and T-cell donor chimerism 50 days after transplantation and related this to disease relapse and overall survival. Methods: 144 sequential patients underwent transplantation of which 90 had AML/MDS and 54 had lymphoma. 'Full donor chimerism' was defined as ≥99% donor cells and three patient groups were defined: 40% with full donor chimerism (FC) in both PBMC and T-cells; 25% with mixed chimerism (MC) within both compartments and 35% with 'split' chimerism (SC) characterised by full donor chimerism within PBMC and mixed chimerism within T-cells. Results: In patients with myeloid disease a pattern of mixed chimerism (MC) was associated with a one year relapse rate of 45% and a five year overall survival of 40% compared to values of 8% and 75%, and 17% and 60%, for those with SC or FC respectively. The pattern of chimerism had no impact on clinical outcome for lymphoma. Conclusion: The pattern of lineage-specific chimerism at 50 days after transplantation is highly predictive of clinical outcome for patients with myeloid malignancy and may help to guide subsequent clinical management.